Contemporary problems of the macroregulation in the economic-ecological sphere and probable solutions (Путеводитель предпринимателя, 2020)
There is bank ofdifferent proposals and theoretical models nowadays which can help solve problems connecting with pollution of the environment. The majority of them is unpromising or complex realizing in practice. It is offered (from the macroeconomic view) to examine interrelation of two processes: the first - economic development, the second - the liquidation of consequences of the environment pollution. Also it is offered to suppose theoretical and practical solutions how to improve mechanisms of macroregulations in ecological sphere.